Characteristics of ultra-high density Al:ZnO sputtering targets prepared by hot isostatic pressing. Issue 5 (1st April 2018) - Gao, Ming; Zhang, Huarui; Xie, Yanjun; Miao, Lei; Yao, Wei; Zhang, Fengge; Wang, Tiejun; Zhang, Hu
Abstract: Ultra-high density large-sized Al:ZnO sputtering targets were prepared by hot isostatic pressing(HIP). Studies were conducted on the characteristics of the microstructure of the targets and the photoelectric properties of the deposited film prepared by medium-frequency magnetron sputtering. Experiments showed that, compared to 98% density target, HIP process had no apparent influence on the change of grain dimension of the targets. However, a reduction of the quantity and size of the porosities in the target matrix was recognized and led to an improvement in the uniformity of resistance and thickness and IR transmittance of the deposited film. In this paper, the favorable machining allowance associated to the thickness of the HIPed targets, due to the oxygen-loss layer, was suggested by developing the empirical formula.